Multi-vector program management for financial system - Бушуєв, Сергій Дмитрович; Ярошенко, Руслан Федорович (Eastern-European Journal of Enterprise Technologies, 2012)
Considering the principles and system architecture of multi-vector program management for financial sector development in turbulence environment. Identifies the key principles of multi-vector methodology of management development programs